Political Constraints and the Limited Effect of Electoral System Change on Personal Vote-Seeking in Hungary. Issue 1 (February 2018) - Papp, Zsófia; Zorigt, Burtejin
This article aims at capturing how the recent changes in Hungary's mixed-member electoral system altered the candidates' personal vote-seeking strategies. Based on the literature, one might expect that strengthening the role of the Single-Member District (SMD) tier increases the incentives for personalisation. By utilizing the data from two consecutive waves of the Comparative Candidate Survey, we show that contrary to these expectations the average level of campaign personalisation decreased from 2010 to 2014. Semi-structured interviews with nine campaign staff members confirm that the political constraints were more important in determining campaign strategies than the institutional setting. Our findings challenge the dominating effect of electoral rules on personal vote-seeking.